Audit firm tenure, auditor familiarity, and trust: Effect on auditee whistleblowing reporting intentions. Issue 2 (5th January 2018) - Wilson, Aaron B.; McNellis, Casey; Latham, Claire Kamm
Abstract : Mandatory audit firm rotation has been researched for decades with resulting opposition as well as support. Research has mainly treated mandatory auditor rotation at the firm macro level. We submit the client relationship length is comprised of firm tenure and audit team continuity, or auditor familiarity. Increased tenure, at the interorganizational or firm level and interpersonal or individual level, has been shown to increase trust; and further, trust is positively related to employee voice, such as speaking up about fraud (whistleblowing). We conduct an experiment examining whether increased audit firm tenure and auditor familiarity leads to increased trust, which enhances the willingness to whistleblow. We find evidence that suggests auditor familiarity enhances trust, which, in turn, positively influences an employee's intentions to whistleblow. This has important implications for the profession and for future research exploring mandatory audit firm rotation; in particular, the need to include auditor familiarity as a construct.